The Causing Factors of Criminal Actions Performed By Children - Andi Dewi Pratiwi (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The decline in the morality of the Indonesian nation regarding sex can be seen in several cases where sex was carried out by celebrities, teachers, civil servants, politicians and students and students without shame. This study aims to find out how much influence porn videos have on children as perpetrators of decency crimes and find out the relevant forms of countermeasures in minimizing the influence of porn videos on children's behavior. This research was conducted at Makassar Polrestabes Class I LAPAS Makassar, and BAPAS Makassar, data collection was carried out by means of interviews and literature study, data were analyzed descriptively. The results of the study show that pornographic videos are a factor that has a stronger influence compared to other factors in decency crimes committed by children. Views in the form of pornographic images will provide sexual stimulation to children. The presence of sexual urges coupled with great curiosity in children has an impact on the occurrence of criminal acts of decency. Efforts to minimize the influence of porn videos in decency crimes committed by children can be carried out in a pre-emitive, preventive and repressive way.